2006
DOI: 10.1103/physrevlett.96.228103
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Diffusion and Percolation in Membranes

Abstract: An algorithm based on Voronoi tessellation and percolation theory is presented to study the diffusion of model membrane components (solutes) in the plasma membrane. The membrane is modeled as a two-dimensional space with integral membrane proteins as static obstacles. The Voronoi diagram consists of vertices, which are equidistant from three matrix obstacles, joined by edges. An edge between two vertices is said to be connected if solute particles can pass directly between the two regions. The percolation thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 26 publications
1
58
0
Order By: Relevance
“…Simple comparison of our results with the results obtained using the continuous model in 2D places them between the results obtained for the Lorentz gas model 33 and the results found using the discontinuous molecular dynamic model. 40 It was also found that the diffusion coefficient for a long time near the percolation threshold scales as D z 3 m where 3 ¼ |c À c c |/c c with m z 4.34. This value of the exponent m is different from the pervious prediction obtained from the percolation theory and simulations, 50 where m ¼ 1.31.…”
Section: Discussionmentioning
confidence: 97%
“…Simple comparison of our results with the results obtained using the continuous model in 2D places them between the results obtained for the Lorentz gas model 33 and the results found using the discontinuous molecular dynamic model. 40 It was also found that the diffusion coefficient for a long time near the percolation threshold scales as D z 3 m where 3 ¼ |c À c c |/c c with m z 4.34. This value of the exponent m is different from the pervious prediction obtained from the percolation theory and simulations, 50 where m ¼ 1.31.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, we perform computations for spheroids whose exact values of α are known. Even though we are not concerned with the critical behavior of the system (the latter was recently studied for overlapping spheres 12,14 and for hard spheres and large-size tracers 15 ), we did perform accurate computations of percolation thresholds because this allowed us to assess the accuracy of approximation (1) without resorting to fitting. Having accurate estimates of V c also made it possible to verify the existence of a universal curve for diffusivities in two and three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent theoretical advancements have extended Saxton's lattice-based results to lattice-free frameworks [30,35,36], including studying the role of obstacle orientation [37]. Progress has also been made by combining experimental and theoretical approaches, for example, studying overlapping circular and elliptical obstacles [38] and studying more complicated environments containing up to 15 different types of obstacles [31].…”
Section: Introductionmentioning
confidence: 97%
“…Such FDE models have been analyzed in various biological settings including chemical reactions [23], reaction fronts [22,24] and reaction-diffusion mechanisms [25]. We would like to emphasize that the group of studies described here, focusing explicitly on motion through crowded environments using experimental and simulation data [30][31][32][33][35][36][37][38][39], have not attempted to interpret their results using any kind of FDE framework. Conversely, the group of studies described here focusing on FDE models [21][22][23][24][25] have not attempted to connect the solution of any FDE model to measurements from any simulation or experiment which explicitly represents transport through a crowded environment.…”
Section: Introductionmentioning
confidence: 98%